Transforming the Housing Process in the Philippines: The Role of Local-Global Networks by the Urban Poor - Karaos, Anna Marie (Archīum Ateneo, 2015)
This chapter investigates the transformation of the housing process in the Philippines as a result of urban poor networking with civil society organizations at the local and transnational levels and with international development agencies and donor organizations. The first part describes the changes that have taken place in the way housing and land security have been provided to informal settler families in the past. It argues that the collaboration strategies among civil society and urban poor groups have contributed to these transformations. It presents the experience of two allied networks that have been working together in mobilizing communities and building local multi-stakeholder partnerships to support community upgrading and housing. This pattern of networking and engagement with government has resulted in new ways of planning and providing housing to the poor. A case in point are the changes that have taken shape in a specific government programme, the housing programme for Informal Settler Families (ISFs) living in danger zones in Metro Manila1 (henceforth, the ISF housing programme). Although limited in geographical scope, because it is being implemented in the national capital region, the ISF housing program provides a template for organizing the housing process in other urban centres of the Philippines. The ISF housing programme contains features incorporated through long-standing advocacy of trans-local urban poor networks in the Philippines such as people’s planning and in-city housing.2 In addition, and more significantly, it is making way for a reordering of governance processes and relations between the urban poor, local governments and other levels of the state. The chapter ends with a consideration of the relevance of networking and what can be considered as the major achievements and the role of local-global actors in shaping local housing processes.